Difference between Leisure and Work Contexts: The Roles of Perceived Enjoyment and Perceived Usefulness in Predicting Mobile Video Calling Use Acceptance - Zhou, Ronggang; Feng, Caihong (Frontiers in Psychology, 2017)
There is a rapidly growing body of literature on mobile video calling, which is one of promising communication technologies; however, little research has focused on user acceptance of mobile video calling, especially in different use contexts. This study explored factors (especially, the perceived enjoyment) influencing the intention of users to employ video calling in different scenarios (a work and a leisure scenario) by applying a Technology Acceptance Model (TAM) combining with the Theory of Planned Behavior (TPB). The revised research model differentiated external factors (subjective norms and personal innovativeness) from internal factors (perceived usefulness, perceived ease of use, perceived enjoyment, and intention to use mobile video calling). In addition, the current study also investigated the predictors of perceived enjoyment across these two scenarios. With the use of a structured questionnaire, participants were divided in two groups and completed self-report measures related to one scenario, and a total of 386 student respondents’ responses were analyzed. Results indicate that users’ intentions are directly predicted by their perceived enjoyment of the video calling (β ≥ 0.35), the call’s perceived usefulness (β ≥ 0.27), and the perceived ease of use (β = 0.13, only for the leisure scenario), which jointly explain at least 55.6% of the variance in use intention. In addition to the effects of these predictors on the mobile video calling use acceptance, an assessment of the moderating effect of different scenarios indicates that perceived enjoyment plays a more important role in influencing intention for the leisure scenario, while perceived usefulness appears to be more important for the work scenario. This study’s findings are important in that they provide strong support for the necessity of distinguishing the different types of scenarios when predicting users’ intention to use video calling. Furthermore, the results show that perceived enjoyment is also significantly influenced by perceived usefulness (β ≥ 0.61), followed by perceived ease of use (β ≥ 0.13). Summarily, the roles of core TAM variables (especially perceived enjoyment and perceived usefulness) as well as external (subjective norms and personal innovativeness) differed in the leisure and work context. The implications of these findings are then discussed.